Ketuban Pecah Dini berhubungan dengan Lama Persalinan dan Asfiksia Neonatorum - Intan Ayu Fransiska; Rosita Khaerina; Kristiani Murti Kisid (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Premature Rupture of  Membranes (PRM) is one of the causes of morbidity in the mother and fetus. The incidence of PRM generally ranges from 10-12% of all pregnancies. Maternal complications caused are intra-amniotic infection, prolonged labor, and postpartum infection. In addition, fetal complications due to PRM are infection, hypoxia and asphyxia, fetal deformity syndrome, and preterm birth. The results of preliminary study, conducted at the Mataram Municipality General Hospital, obtained data on the incidence of PRM in 2022 totaling 301 cases (10,2%) of 2.926 deliveries. Objective: To determine the correlation between premature rupture of membranes and duration of labor and asphyxia neonatorum at Mataram Municipality General Hospital. Method: The population in this study were mothers with PRM as many as 301 respondents. The sampling technique used purpossive sampling with a total sample of 92 respondents. The research design used cross-sectional with data processing techniques using the Chi-square test with the support of SPSS. The research instruments were delivery room registers and medical records. Results: The frequency distributin of PRM showed that mostof the respondents experienced PRM ≤12 hours, which was 70 (76,1%). Respondents with appropriate duration of labor were 83 (90,2%), and 69 (75%) of resondents gave birth to babies who did not have asphyxia neonatorum. The results of PRM statistical test with the duration of labor showed no correlation with a p –value of 0,90 (> 0,05). The results of the PRM statistical test with asphyxia neonatorum showed a significant p-value mof 0,00 (<0,05). Conclusion: There is no correlation between PRM and the duration of labor and there is a correlation between PRM and asphyxia neonatorum. The duration of labor in PRM patients is affected by the management carried out at the Mataram Municipality General Hospital to reduce the risk of prolonged labor.